2014
DOI: 10.3102/0002831214541046
|View full text |Cite
|
Sign up to set email alerts
|

Does School Policy Affect Housing Choices? Evidence From the End of Desegregation in Charlotte–Mecklenburg

Abstract: We examine whether the legal decision to grant unitary status to the Charlotte–Mecklenburg school district, which led to the end of race-conscious student assignment policies, increased the probability that families with children enrolled in the district would move to neighborhoods with a greater proportion of student residents of the same race as their own children. Motivated by the rich but inconclusive literature on the consequences of educational and residential segregation, we make use of a natural policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Since education is a key commodity, political leaders of homogeneous suburban communities work to maintain exclusionary boundaries in the hopes of attracting new residents (Buendía & Humbert-Fisk, 2015). While comprehensive school desegregation plans that de-emphasize urban-suburban boundaries can mitigate white flight (Green, 1985; Orfield, 2001; Orfield & Frankenberg, 2014), a recent causal study of Charlotte-Mecklenburg, North Carolina, found that once such plans end, white families are considerably more inclined to move to a neighborhood (and school) with higher shares of other whites (Liebowitz & Page, 2014). In fragmented metropolitan areas with numerous school districts, the boundary lines that separate central city districts from multiple suburban ones partly explain high levels of school segregation between districts (Bischoff, 2008; Fiel, 2013, 2015; Frankenberg, 2009; Reardon, Yun, & Eitle, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since education is a key commodity, political leaders of homogeneous suburban communities work to maintain exclusionary boundaries in the hopes of attracting new residents (Buendía & Humbert-Fisk, 2015). While comprehensive school desegregation plans that de-emphasize urban-suburban boundaries can mitigate white flight (Green, 1985; Orfield, 2001; Orfield & Frankenberg, 2014), a recent causal study of Charlotte-Mecklenburg, North Carolina, found that once such plans end, white families are considerably more inclined to move to a neighborhood (and school) with higher shares of other whites (Liebowitz & Page, 2014). In fragmented metropolitan areas with numerous school districts, the boundary lines that separate central city districts from multiple suburban ones partly explain high levels of school segregation between districts (Bischoff, 2008; Fiel, 2013, 2015; Frankenberg, 2009; Reardon, Yun, & Eitle, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weinstein (2011) and Liebowitz and Page (2012) study neighborhood change in Charlotte following the end of busing. Weinstein (2011) finds that a 10 percentage point increase in the percent black of an assigned elementary school led to a 0.4 percentage point change in the percent minority of the neighborhood five years after busing.…”
Section: Vib Peer Effectsmentioning
confidence: 99%
“…These school attendance boundary decisions can fuel both school and residential segregation. For example, if a school district zones a subsidized housing property to a racially isolated and/or low-income school, these decisions can worsen not only school segregation, but also fuel segregation in neighborhoods around affordable housing properties, as white and middle-class families often seek to avoid housing near such schools (Holme, 2002;Lareau & Goyette, 2014;Liebowitz & Page, 2014…”
Section: The Role Of Local Jurisdictionsmentioning
confidence: 99%